2021
DOI: 10.1097/pai.0000000000000929
|View full text |Cite
|
Sign up to set email alerts
|

MLH1, MSH2, MRE11, and XRCC1 in Oral Leukoplakia and Oral Squamous Cell Carcinoma

Abstract: Background: DNA damage is accumulated in the cells over time as the result of both exogenous and endogenous factors. The objective of this study was to analyze the immunohistochemical expression of the repair proteins in oral leukoplakia (OL) and oral squamous cell carcinoma (OSCC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In multiple gastric cancers (MGC) characterized by the presence of more than two different tumors in the stomach, the MSH2 mutations, particularly germline MSH2 X314 _splice variants, may contribute to carcinogenesis, suggesting the consideration of more radical surgery and/or anti-PD-1/PD-L1 therapy ( Wang et al, 2020 ). In oral diseases, the study supports that patients with MSH2 overexpression may easily present with oral squamous cell carcinoma ( Donís et al, 2021 ). Moreover, MSH2 mutation was found in 31% of patients with Lynch syndrome-associated GBMs, indicating that MSH2 may play important role in the progression of GBM ( Kim et al, 2022 ).…”
Section: Discussionsupporting
confidence: 68%
“…In multiple gastric cancers (MGC) characterized by the presence of more than two different tumors in the stomach, the MSH2 mutations, particularly germline MSH2 X314 _splice variants, may contribute to carcinogenesis, suggesting the consideration of more radical surgery and/or anti-PD-1/PD-L1 therapy ( Wang et al, 2020 ). In oral diseases, the study supports that patients with MSH2 overexpression may easily present with oral squamous cell carcinoma ( Donís et al, 2021 ). Moreover, MSH2 mutation was found in 31% of patients with Lynch syndrome-associated GBMs, indicating that MSH2 may play important role in the progression of GBM ( Kim et al, 2022 ).…”
Section: Discussionsupporting
confidence: 68%
“…DNA repair genes over-expressed in constant ph -KD tumors include several components previously linked to damage accumulation, cancer formation, and/or poor cancer prognosis ( Table 1 ), like Mms4 ( Dewalt, Kesler et al 2014 ), RecQ4 ( Maire, Yoshimoto et al 2009 , Su, Meador et al 2010 , Xu, Chang et al 2021 ), PolH ( Tomicic, Aasland et al 2014 , Sonobe, Yang et al 2024 ), Tipin/Timeless ( Zhou, Zhang et al 2020 , Chen, Zhang et al 2022 ), Claspin ( Choi, Yang et al 2014 ), MRNIP ( Staples, Barone et al 2016 , Bennett, Wilkie et al 2020 , Wang, Zhao et al 2022 ), FANCI ( Smogorzewska, Matsuoka et al 2007 , Li, Yu et al 2023 ), MMR proteins (Msh2, Mlh1, Msh6) ( Shcherbakova and Kunkel 1999 , Velasco, Albert et al 2002 , Li, Liu et al 2008 , Wagner, Webber et al 2016 , Wilczak, Rashed et al 2017 , Chakraborty, Dinh and Alani 2018 , Donis, Gonzalez et al 2021 , Zhou, Xiao and Chen 2024 ), and Rif1 ( Liu, Mei et al 2018 , Mei, Liu et al 2018 , Sad, Mohamed et al 2021 ). Similarly, genes down regulated in constant ph -KD tumors include known components required for DNA repair and replication fork protection in the presence of replication damage, like the PCNA variant PCNA2 ( Feng, Xia et al 2023 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…MSH2 is an essential part of the DNA mismatch repair system for DNA damage repairment [ 23 , 24 ]. According to the previous reports, the expression MSH2 was increased in oral squamous cell carcinoma and decreased in breast and gastric cancer [ 19 , 25 , 26 ]. MSH2 may have a functional consequence in different types of cancer, which is worthy of our further study.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that MSH2 expression is increased in low-grade and high-grade urothelial malignancy [ 27 ]. In addition, MSH2 was overexpressed in patients with colon cancer and oral squamous cell carcinoma [ 19 , 28 ]. The research results showed above agreeing with our conclusions.…”
Section: Discussionmentioning
confidence: 99%